2009
DOI: 10.1007/978-90-481-3471-7_14
|View full text |Cite
|
Sign up to set email alerts
|

Nonhomologous DNA End Joining (NHEJ) and Chromosomal Translocations in Humans

Abstract: Estimates are that double-strand breaks (DSBs) arise in dividing cells about ten times per cell per day. Causes include replication across a nick, free radicals of oxidative metabolism, ionizing radiation, and inadvertent action by enzymes of DNA metabolism (such as failures of type II topoisomerases or cleavage by recombinases at pseudo sequences that look sufficiently similar to the physiologic ones). There are two major double-strand break repair pathways. Homologous recombination (HR) can repair double-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 59 publications
0
81
0
3
Order By: Relevance
“…Pharmacological inhibition of CTSS significantly reduced experimental breast cancer metastasis and tumor development [54], suggesting its potential as a therapeutic target for this disease. In this study, we also demonstrated that pharmacological inhibition of CTSS suppresses BRCA1 degradation and restores BRCA1 function, providing supporting evidence for CTSS as a potential target for anticancer therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Pharmacological inhibition of CTSS significantly reduced experimental breast cancer metastasis and tumor development [54], suggesting its potential as a therapeutic target for this disease. In this study, we also demonstrated that pharmacological inhibition of CTSS suppresses BRCA1 degradation and restores BRCA1 function, providing supporting evidence for CTSS as a potential target for anticancer therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Bulky DNA adducts are processed through the nucleotide excision repair pathway (NER) [14][15][16]. DNA double strand breaks are repaired through the homologous recombination pathway (predominantly during S-phase of cell cycle) [17][18][19] or the non-homologous end joining pathway (NHEJ), that operates outside the S-phase of the cell cycle [20][21][22]. DNA base damage is processed by the base excision repair (BER) machinery.…”
Section: Introductionmentioning
confidence: 99%
“…DNA double-strand breaks (DSBs) are the most severe type of DNA lesions that can be caused by various exogenous and endogenous mechanisms, such as ionizing radiation, reactive oxygen species, topoisomerase poisons, or replication errors [1]. DSBs, if left unrepaired or mis-repaired, lead to cell death or chromosomal aberrations [2,3].…”
mentioning
confidence: 99%